1994
DOI: 10.1161/01.str.25.8.1574
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow velocity and vasomotor reactivity in patients with arteriovenous malformations. A transcranial Doppler study.

Abstract: Background and Purpose A large percentage of patients with a cerebral arteriovenous malformation (AVM) show focal neurological signs or have a history of intracranial hemorrhage. The present study used transcranial Doppler sonography to assess the clinical significance of hemodynamic disturbances in the intracranial arteries of patients with an AVM.Methods Eighteen patients with untreated AVMs were examined clinically, angiographically, and with transcranial Doppler sonography (blood flow velocity measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…NPPB theory rests on the assumption that lost autoregulatory capacity persists following resection of a cerebral AVM. Nevertheless, several studies demonstrate a postoperative return to normal CO2 reactivity in vessels with previously diminished reactivity [3,[10][11][12][13][14][15][16] . Young et al [12,13] showed intact CO2 reactivity both before and after resection.…”
Section: Discussionmentioning
confidence: 99%
“…NPPB theory rests on the assumption that lost autoregulatory capacity persists following resection of a cerebral AVM. Nevertheless, several studies demonstrate a postoperative return to normal CO2 reactivity in vessels with previously diminished reactivity [3,[10][11][12][13][14][15][16] . Young et al [12,13] showed intact CO2 reactivity both before and after resection.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to measure CBF quantitatively with sufficient temporal and spatial resolution in a clinical setting has resulted in the use of substitutes such as blood flow velocity 3,8 or HbO 2 with nearly infrared spectroscopy (NIRS). 10,11 We have adopted the latter approach because Smielewski et al 10,11 have shown that HbO 2 changes after induced alterations in CO 2 allow valid assessment of CVR.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in studies using transcranial Doppler, one has to take into account which vessels were insonated. In one study, the results were considered indicative of pathological vasoreactivity without clearly stating whether these arteries were involved in AVM supply, 3 whereas other authors found evidence for intact CVR in nonfeeding arteries with transcranial Doppler sonography 8 or intraoperative micro-Doppler. 7 Other authors found impaired CVR and hyperresponsiveness to vasodilative stimuli and thought that they were predictive of the occurrence of postoperative hyperemic complications.…”
Section: Preoperative Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diehl et al [24] reported a pathological increase in blood flow velocity (57.6%) and a decrease in vasomotor reactivity (72.7%) were frequently found in AVM feeding arteries. Vasomotor reactivity was also reduced in several nonfeeding arteries both ipsilateral (53.3%) and contralateral (30.8%) to the AVM.…”
Section: Avmsmentioning
confidence: 96%